2021
DOI: 10.5585/iji.v9i3.20286
|View full text |Cite
|
Sign up to set email alerts
|

A game to teach and apply design thinking for innovation

Abstract: Objective: Develop and apply a game to facilitate the use of design thinking for innovation.Method: The construction of the game was based upon the Constructivism Theory. The game was developed following the steps of: (i) understanding the target audience and the context; (ii) defining learning objectives; (iii) structuring the experience; (iv) identifying resources and applying gamification elements; (v) evaluation. Originality/Relevance: Design Thinking emerges as an alternative to improve the innovation pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Game developers constantly strive to enhance their products' performance and quality, resulting in innovation and invention. Purchase intention is primarily influenced by consumers' perception of performance and quality values (Kloeckner et al 2021). Previous studies have demonstrated that quality can have a moderate impact on behavioral intentions through perceived value and satisfaction (Ghazali et al (2019), or it can have a direct impact.…”
Section: Social Valuementioning
confidence: 99%
“…Game developers constantly strive to enhance their products' performance and quality, resulting in innovation and invention. Purchase intention is primarily influenced by consumers' perception of performance and quality values (Kloeckner et al 2021). Previous studies have demonstrated that quality can have a moderate impact on behavioral intentions through perceived value and satisfaction (Ghazali et al (2019), or it can have a direct impact.…”
Section: Social Valuementioning
confidence: 99%
“…Before those, however, let's admit that our separation of Tier A and Tier B (learning from playing games vs learning from creating games) will not cleanly classify all gamification approaches. For example, the design game created by Kloeckner et al [26] gamifies a general design process whose design products are educational materials (such as an architectural design portfolio structure) but which they say could also be games. In this case, depending on whether the output is a game or not, we could say that their method spans both Tier A and Tier B, or stays in Tier A.…”
Section: Related Workmentioning
confidence: 99%